Pengembangan Usaha Jasa Laundry dalam Meningkatkan Pendapatan Marginal rumah tangga dalam Perspektif Ekonomi Islam di Watampone (Studi Pada Octa Laundry) - Rahayu Bahri; Hj. Naharia Hj. Naharia (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This study discusses the development of laundry services business in increasing marginal income in the perspective of Islamic economics, the main problem in this study is how business development is carried out in increasing income in Octa laundry business. This study aims to determine the business development carried out by Octa Laundry, the contribution of business development carried out by Octa Laundry in increasing household marginal income, and Islamic economic perspective on business development carried out on Octa laundry. The type of research used is qualitative research with an approach Islamic economics. The subjects in this study were the owners and workers of Octa Laundry, while the object of the research was the development of businesses and the marginal income of households received from laundry businesses. The data collection techniques used are the method of observation (observation), interviews, and documentation. The collected data is then processed and analyzed using qualitative descriptive techniques. The results of the study show that in business development carried out on Octa laundry, generally using three production factors including capital in the form of money and equipment, labor, and entrepreneurial skills.